2005
DOI: 10.1128/jvi.79.8.4944-4951.2005
|View full text |Cite
|
Sign up to set email alerts
|

CD4-Independent Entry and Replication of Simian Immunodeficiency Virus in Primary Rhesus Macaque Astrocytes Are Regulated by the Transmembrane Protein

Abstract: Previous studies have demonstrated that the genetic determinants of simian immunodeficiency virus (SIV) neurovirulence map to the env and nef genes. Recent studies from our laboratory demonstrated that SIV replication in primary rhesus macaque astrocyte cultures is dependent upon the nef gene. Here, we demonstrate that macrophage tropism is not sufficient for replication in astrocytes and that specific amino acids in the transmembrane (TM) portion of Env are also important for optimal SIV replication in astroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…Similar results were reported in a recent study by Gonzalez-Scarano and colleagues [83]. These observations together with the finding that BORI-15 and UK1-br induce multinucleated giant cells in MDM and UK1-br induces neuronal apoptosis in primary brain cultures [56,129] and the observation that neurovirulent CCR5-tropic SHIVs are CD4-independent [15,33,103] suggest that viruses with increased affinity for the CD4/CCR5 complex and/or reduced CCR5/CD4 dependence have increased neurotropism and pathogenicity in the CNS. Similarly, a pathogenic SHIV variant that is neurotropic and uses CXCR4 has reduced dependence on CD4/CXCR4 [130].…”
Section: Reduced Ccr5/cd4 Dependence Of Neuro-tropic Hiv and Role In supporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were reported in a recent study by Gonzalez-Scarano and colleagues [83]. These observations together with the finding that BORI-15 and UK1-br induce multinucleated giant cells in MDM and UK1-br induces neuronal apoptosis in primary brain cultures [56,129] and the observation that neurovirulent CCR5-tropic SHIVs are CD4-independent [15,33,103] suggest that viruses with increased affinity for the CD4/CCR5 complex and/or reduced CCR5/CD4 dependence have increased neurotropism and pathogenicity in the CNS. Similarly, a pathogenic SHIV variant that is neurotropic and uses CXCR4 has reduced dependence on CD4/CXCR4 [130].…”
Section: Reduced Ccr5/cd4 Dependence Of Neuro-tropic Hiv and Role In supporting
confidence: 89%
“…Other studies of HIV or SIV Envs also mapped determinants of reduced CD4 dependence or CD4 independence to the V1V2 regions [20,70,115,116,155]. However, additional determinants in the V3 and V4 regions and in gp41 can also contribute to reduced CD4 dependence or CD4 independence, with the specific determinants being strain-specific [15,20,32,73,102,103,115].…”
Section: Reduced Ccr5/cd4 Dependence Of Neuro-tropic Hiv and Role In mentioning
confidence: 92%
“…for mRNA analysis. As we and other groups have shown (39, 40), while virus infection in macrophages takes place during the course of days, infection in astrocytes takes longer because restrictive factors specific to this cell type severely slows down viral replication in vitro . (Figures 1A and 2A).…”
Section: Resultsmentioning
confidence: 72%
“…Primary rhesus macaque astrocytes (Cambrex, Walkersville MD) were cultured as previously described (39). Cells were infected with SIV/17E-Fr at an MOI of 0.05 for 6 hours and then washed 3 times with sterile PBS.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, although we identified these gp41 truncations in only one of the two conventional progressors in this study, we previously reported the presence of similar truncations in isolates from the brain of the original SIVsmE543-infected animal (45). In addition, other studies using well-characterized neurovirulent SIV clones demonstrated that a similar truncation at the TM domain of gp41 is responsible for CD4 independence (46,47). These observations suggest that those gp41 truncations may play important roles in the pathogenesis of SIV in the CNS.…”
Section: Figmentioning
confidence: 76%